Realistic warpage evaluation of printed board assembly during reflow process. Issue 4 (7th September 2015) - Chung, Soonwan; Kwak, Jae B.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to develop an estimation tool for warpage behavior of slim printed circuit board (PCB) array while soldering with electronic components by using finite element method. One of the essential requirements for handheld devices, such as smart phone, digital camera, and Note-PC, is the slim design to satisfy the customers' desires. Accordingly, the printed circuit board (PCB) should be also thinner for a slim appearance, which would result in decreasing the PCB's bending stiffness. This means that PCB deforms severely during the reflow (soldering) process where the peak temperature goes up to 250°C. Therefore, it is important to estimate PCB deformation at a high temperature for thermo-mechanical quality/reliability after reflow process. Design/methodology/approach – A numerical simulation technique was devised and customized to accurately estimate the behavior of a thin printed board assembly (PBA) during reflow by considering all components, including PCB, microelectronic packages and solder interconnects. Findings – By applying appropriate constraints and boundary conditions, it was found that PBA's warpage can be accurately predicted during the reflow process. The results were also validated by warpage measurement, which showed a fairly good agreement with one and another. Research limitations/implications – For research limitations, there are many assumptions regarding numerical modeling. That is, the viscoplastic material property of solder ball is ignored, the reflow profile is simplified and the accurate heat capacity is not considered. Furthermore, the residual stress within the PCB, generated at PCB manufacturing process, is not included in this paper. Practical implications – This paper shows how to calculate PBA warpage during the reflow process as accurately as possible. This methodology helps a PCB designer and surface-mount technology (SMT) process manager to predict a PBA warpage issue and modify PCB design before PCB real fabrication. Practically, this modeling and simulation process can be easily performed by using a graphical user interface (GUI) module, so that the engineer can handle an issue by inputting some numbers and clicking some buttons. Social implications – In a common sense manner, a numerical simulation method can decrease time and cost in manufacturing real samples. This PCB warpage method can also decrease product development duration and produce a new product earlier. Furthermore, PCB is a common component in all the electronic devices. So, this PCB warpage method can have various applications. Originality/value – Because of an economic advantage, the development of a numerical simulation tool for estimating the thin PBA warpage behaviour during reflow process was attempted. The developed tool contains the features of detailed modeling for electronic components and contact boundary conditions of the supporting rails in the reflow oven.